Avaliação da sustentabilidade dos programas de financiamento rural para o desenvolvimento rural do estado do Ceará: Um estudo de caso - Miranda, Izabel Cristina Alves (2008)
The subsidized agricultural credit is one of the instruments used for the Government in the search of increase of the production and in the modernization of farming, agro-industrial units and in the improvement in the qualilty of life of the small agricultural producer. Managed by (BNB) Banco do Nordeste do Brasil, (FNE) Northeast Constitucional Leasing Fund (FNE) is a source guaranted by Federal Government, therefore adjusted to medium term as well as long terms leasing projects in order to develop the Region. Among many FNE credits there is RURAL FNE, our researching objects, RURAL FNE is a Federal Government aiding farm enterprising settlement, extension, diversification and modernization, using machine, equipment and farming cost investiment projects leasing. The program has as agricultural producers (farmars or companies), as well as farmer cooperatives and associations. The goal of this is study is to measure the sustainability of farmers supported by RURAL FNE, Through a case in the city of Limoeiro do Norte – CE, considering: social, economic, financial, environmental and employment aspects in order to try to find possible obstacles that can be surpassed in order to have farming sustainability. There was interviews with ones receiving RURAL FNE, RURAL FNE +PRONAF and PRONAF as well asthe one without leasing. The sustainability rate of RURAL-FNE farmers (0,577) was the highest ona among all the productive sectors because those ones were rated as medium level of sustainability. The ones without leasing 0,485 were rated as under the sustainability level. Socioeconomics and environmental rates were considered as the highest and the lowest ones on IS composition, respectively. Farmers with RURAL-FNE leasing were the biggest employers even over average of interviewed farmers. The goal presented suggestions is keep farmers aware about the importance of environment with lessons of ambient education; supporting them opn the preparation as well as the soil manuntence; aiding their family members teaching agroecology leading the society to recognize how much important slight konwledge tracing way for a conscientious society of the importance the sustainable agriculture is.